Problematika Penerimaan Peserta Didik Baru (PPDB) pada Masa Pandemi Covid-19 di SMP Negeri 1 Sangatta Utara - Asidah, Nur; Nurtantiani, Nurtantiani; Zahratunnisa, Firdha; Rosyidah, Irma; Risma Putri, Desmaniar (Jayapangus Press, 2022)
This study describes the problems of new student admissions (PPDB) at SMP Negeri 1 Sangatta Utara during the covid-19 pandemic. This is a system designed to make selections starting from registration, the selection process to the selection announcement process. The PPDB system is expected to be able to meet public expectations regarding the implementation of objective and transparent new student admissions. This study was conducted to describe the management of new student admissions at SMP Negeri 1 Sangatta Utara, including planning, procedures, implementation, control, factors supporting success and inhibiting factors. The methods used in this study are (1) a qualitative descriptive approach, (2) the location of the study was carried out at SMP Negeri 1 Sangatta Utara, (3) data was obtained from vice principals, and teachers (4) Data was collected by in-depth interviews, and observation, documentation (5) The data were analyzed descriptively with interactive analysis, namely data condensation, data presentation, and drawing and drawing conclusions. The results of the study indicate that the problems of PPDB at SMP Negeri 1 Sangatta Utara, among others 1) are not yet ready for prospective students who use the online/online system. Considering that the previous academic year was held manually, when in conditions of the implementation of restrictions on community activities due to the COVID-19 pandemic, it felt awkward, surprised and seemed unprepared. 2) differences in school status, when accepting new students from schools under the auspices of the ministry of religion, for example from madrasah Ibtidaiyah, it is difficult because of differences in parent numbers, whereas from public schools using NISN. And number 3) is the lack of maximum socialization techniques applied.